Natural Abundance Oxygen-17 NMR Investigation of Lithium Ion Solvation in Glyme-based Electrolytes. (20th September 2016) - Peng, Jing; Carbone, Lorenzo; Gobet, Mallory; Hassoun, Jusef; Devany, Matthew; Greenbaum, Steven
Abstract: In this report, the lithium solvation behavior of two series of glyme-based electrolytes, with lithium trifluoromethanesulfonate (LiTf) or lithium-bis-(trifluormethanesulfonyl)-imide (LiTFSI) in six glymes with different chain length, is characterized using natural abundance oxygen-17 ( 17 O) NMR spectroscopy. The effect of salt addition on chemical shift is observed by comparing the 17 O NMR spectra of electrolytes and their corresponding neat solvents. The study reveals a more pronounced effect of the salt addition on the chemical shift of ether oxygens compared to terminal oxygens of glymes, thus suggesting a preferential coordination of Li + with the ether oxygens. The 17 O NMR data exhibit decreasing chemical shift changes with increasing chain length of glymes due to the increased number of ether oxygens coordinating each Li + in the electrolytes. In addition, the trend of anion oxygen chemical shift, particularly for Tf − anion, suggests an effect of the chain length on the ion association degree. The results illustrate the sensitivity of 17 O NMR to subtle changes in the ion-solvent and ion–ion interactions.